2019
DOI: 10.2533/chimia.2019.561
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the Potential Role of Metabolites on the Anti-Leukemic Activity of Imatinib, Nilotinib and Midostaurin

Abstract: The efficacy and side-effects of drugs do not just reflect the biochemical and pharmacodynamic properties of the parent compound, but often comprise of cooperative effects between the properties of the parent and active metabolites. Metabolites of imatinib, nilotinib and midostaurin have been synthesised and evaluated in assays to compare their properties as protein kinase inhibitors with the parent drugs. The N-desmethyl-metabolite of imatinib is substantially less active than imatinib as a BCR-ABL1 kinase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Mlejnek et al also found that N-demethyl IM had almost no therapeutic effect on CML through K562 cell experiments [17]. In addition, some studies have shown that some metabolic compounds, especially highly demethylated and sulfur-containing compounds (M15 and M24 in this experiment) may be related to IM adverse reactions [24,26].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Mlejnek et al also found that N-demethyl IM had almost no therapeutic effect on CML through K562 cell experiments [17]. In addition, some studies have shown that some metabolic compounds, especially highly demethylated and sulfur-containing compounds (M15 and M24 in this experiment) may be related to IM adverse reactions [24,26].…”
Section: Discussionmentioning
confidence: 55%
“…With regard to the effect of IM metabolites, N-demethylated metabolites of IM (M15 in this experiment) were the main metabolites of IM, although they had similar effects. However, some studies have shown that the pharmacological activity of N-demethyl IM was three times lower than that of IM [26]. Mlejnek et al also found that N-demethyl IM had almost no therapeutic effect on CML through K562 cell experiments [17].…”
Section: Discussionmentioning
confidence: 99%
“…In order to predict the stability and strength of interaction of different drugs with RUNX1, an AML drug specific target, we performed molecular docking of standard published Abemaciclib ( Gelbert et al, 2014 ), Cisplatin ( Dasari and Tchounwou 2014 ), Dacarbazine ( Serrone et al, 2000 ) Enasidenib ( Del Principe et al, 2019 ) Gefitinib ( Baselga and Averbuch 2000 ), Gilteritinib ( Lee et al, 2017 ; McMahon and Perl 2019 ) Ibrutinib ( Honigberg et al, 2010 ) Lenvatinib/Pembrolizumab ( Makker et al, 2019 ), Midostaurin ( Manley 2019 ), Zejula (niraparib), Regorafenib ( Carr et al, 2013 ), Sorafenib ( Hotte and Hirte 2002 ), and Triclabendazole ( Fetterer 1986 ), are employed to treat various cancers—with two being used towards lowering the activity of a corresponding transcription factor in treating AML ( Table 1 ). However, these drugs’ activities and their molecular consequences have not been previously considered in the context of RUNX1-ETS DNA complex.…”
Section: Resultsmentioning
confidence: 99%
“…27,28 The prototype drug imatinib and its advancer nilotinib are very potent, competitive Bcr-Abl tyrosine kinase inhibitors (TKIs), which act on the ATP binding site in the catalytic domain of the Abl kinase. 25,29,30 The latter consists of several regionsa hydrophobic pocket, a hydrophobic channel, an adenine, a sugar, and a phosphate-binding region. 31 Crucial structural elements for the active site binding interactions are: the pyridyl-pyrimidine fragment in the hydrophobic pocket of the hinge region; the aniline-NH hydrogen bonding with the Thr315 gatekeeper residue; and the aromatic amide bond serving as an anchoring group.…”
Section: Introductionmentioning
confidence: 99%
“…1) represents a milestone in the field of oncopharmacology, giving birth to genome-targeted anticancer therapies. 25 The presence of site-specific mutations in various proliferative diseases makes the molecular profiling of tumor pathology possible, thus giving specific protein drug targets to medicinal chemists. 26 Chronic myeloid leukemia (CML) is a hematopoietic disorder characterized by a pathognomonic reciprocal translocation between chromosomes 9 and 22: t (9;22)(q34;q11), resulting in the formation of a fusion Bcr–Abl oncoprotein.…”
Section: Introductionmentioning
confidence: 99%